Peningkatan Keterampilan Olahraga Volly dan Management Event Tournament Volley Ball SDN 020 Pulau Godang Kari Tingkat Kecamatan Kuantan Tengah - Annisa Dwi Rahmadhani; Fauzy Rahendra; Ahmad Al Hafiz Munthe; Bayu Adrian Hidayat; Safitriyanti Safitriyanti; Yulia Yusari; Muhammad Ilham Habibi; Najib Umbara S; Risan Hanudin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The purpose of this activity is as an effort to improve the volleyball skills of students and teachers throughout Kuantan Tengah District, the time and place of implementation is Wednesday, August 14 2024, 08.00-12.00 WIB and located at the volleyball hall of SDN 020 Pulau Godang Kari as the host. House. Event Management is the process of planning, organizing and implementing events with the aim of creating a memorable experience for event participants. Many things are regulated in event management, such as determining location, budget, marketing, logistics, security and other operational activities. In the context of this tournament event, event management is very important to ensure that all elements of the event run smoothly and according to participants' expectations. Therefore, we as members of the Pulau Godang Kari Village KKN together with the Teachers of SDN 020 Pulau Godang Kari collaborated in making this event a success.